Characteristic of in-work poverty – a comparison between Romania and European Union - Ghența, Mihaela (Journal of Economic Development, Environment and People, 2017)
The aim of this article is to analyse the characteristics of the working poor in Romania compared to other European Member States. In-work poverty is an important aspect in the discussions regarding the effectiveness of employment in preventing the risk of poverty. The in-work poverty is the result of several factors among which we mention those related to the individual characteristics, household composition, and labour market policies. In Romania, the level of in-work poverty continues to remain high for the overall employed population aged 18 years and over and this evolution is due to the part-time working program, the temporary contracts, and the low level of education. The last part of the article presents the measures identified in the scientific literature to reduce the in-work poverty.